New species of Microcentrum Scudder, 1862 (Orthoptera: Tettigonioidea: Phaneropteridae) from Amazon rainforest - Da Silva Sovano, Rafael S.; Cadena-Castañeda, Oscar J. (Zootaxa, 2015)
A regional study is performed for the Amazonian species of the genus Microcentrum Scudder, 1862, its proposed Microcentrum punctifrons Brunner von Wattenwyl, 1891 as nomen dubium n. stat. and two new species are described: Microcentrum amacayacu Cadena-Casteñada, Sovano n. sp. and Microcentrum xavieri Sovano, Cadena-Casteñada n. sp. the Colombian and Brazilian Amazon, respectively. A list and a key to the Amazonian species are also provided, along with a discussion on their distribution, according to endemism areas established to Amazon rainforest.